2017
DOI: 10.1038/srep40402
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Cyclocarya paliurus polysaccharides markedly attenuates inflammation and oxidative damage in lipopolysaccharide-treated macrophage cells and mice

Abstract: Natural polysaccharides and their modified derivatives are crucial supplements to the prevention of inflammation. This study aimed to evaluate the effect of sulfated modification on the anti-inflammatory and anti-oxidative activities of Cyclocarya paliurus polysaccharides (CP). A sulfated CP, S-CP1–4 was obtained using chlorosulfonic acid-pyridine method. The chemical components and FT-IR spectrum confirmed that sulfated group was synthesized to the polysaccharide chains successfully. S-CP1–4 was found to inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 61 publications
1
39
0
Order By: Relevance
“…Because LPS induced RAW264.7 macrophage cells to polarize into M1 phenotype, our results showed that M1 phenotype macrophages (LPS treated macrophages) exhibited higher level of phagocytosis (Figure ). However, excess phagocytosis could cause inflammation and do harm to organs (Wang, Xie, et al, ). In our study, PSPPs treatment inhibited the excessive phagocytosis level as compared with LPS treated group ( p < .05).…”
Section: Discussionmentioning
confidence: 99%
“…Because LPS induced RAW264.7 macrophage cells to polarize into M1 phenotype, our results showed that M1 phenotype macrophages (LPS treated macrophages) exhibited higher level of phagocytosis (Figure ). However, excess phagocytosis could cause inflammation and do harm to organs (Wang, Xie, et al, ). In our study, PSPPs treatment inhibited the excessive phagocytosis level as compared with LPS treated group ( p < .05).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inflammatory molecules can be a potential thyroid cancer treatment target, while immunotherapy gradually become the focus in the treatment of thyroid cancer in recent years. As reported, qing qian liu polysaccharide has been proven to have the function of immune regulation and can inhibit the release of IL-6 and TNF-β by macrophages stimulated by LPS [16]. Cyclocarya paliurus polysaccharide is a kind of natural plant polysaccharide extracted from Cyclocarya paliurus.…”
Section: Discussionmentioning
confidence: 99%
“…The marine sourced sulfated polysaccharides have established anti-oxidative, antimicrobial, anticoagulant, and anticancer activities (Freudenberg et al, 2015; Song et al, 2015; Fernando et al, 2016; Prasedya et al, 2016; Wang et al, 2017). Biomaterial developed here capitalizes on the favorable properties of these individual components to regulate microenvironment thereby acting synergistically to promote healing.…”
Section: Discussionmentioning
confidence: 99%